2010
DOI: 10.4037/ajcc2010967
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Comorbid Psychiatric Conditions and Mortality in Nonsurgical Intensive Care Patients

Abstract: Purpose To examine the effects of preexisting comorbid psychiatric conditions on mortality in a large cohort of patients admitted to a nonsurgical intensive care unit. Methods This retrospective cohort study involved 66 672 consecutive eligible nonsurgical patients admitted to intensive care units in 129 Veterans Health Administration hospitals during 2005 and 2006. Preexisting comorbid psychiatric conditions were identified by using diagnoses from outpatient encounters in the prior year for depression, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…As demonstrated by Abrams et al, the method utilized to identify mental illness can have a significant impact on observed results. 14, 15, 25 Using outpatient records resulted in a significant association between SMI and 30-day mortality in Veteran’s Health Administration hospital patients, while using inpatient records did not. However, it is also important to note that many previous studies examining outcomes of patients with SMI were conducted in different study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by Abrams et al, the method utilized to identify mental illness can have a significant impact on observed results. 14, 15, 25 Using outpatient records resulted in a significant association between SMI and 30-day mortality in Veteran’s Health Administration hospital patients, while using inpatient records did not. However, it is also important to note that many previous studies examining outcomes of patients with SMI were conducted in different study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of Abrams et al who observed that comorbid psychiatric conditions identified using hospital inpatient records were not associated with 30-day mortality in Veteran’s Health Administration hospital patients admitted for acute myocardial infarction or nonsurgical intensive care. 14, 15 Furthermore, Blecker et al (2010) observed no association between SMI and quality of care, including hospital readmission, in disabled Medicaid recipients with heart failure. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers speculate that effects of psychiatric comorbidity on doctor-patient communication might play a role [14], and psychological or social factors associated with PTSD as either risk factors or symptoms might influence how timely and successfully a patient responds to symptoms of illness, influencing their clinical course [47,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Costs of patients with PTSD exceed the costs of patients without PTSD by between 8% and 75% when PTSD occurred as a result of traffic accidents [11,12], and there is some evidence that poor psychological health and psychological disorders, such as PTSD, complicate clinical course even in routine surgical procedures [13]. Yet there are dissenting findings how PTSD affects the clinical course [14]. In a study assessing patients admitted to a Level I Trauma Centre, post-traumatic stress syndrome (PTSS) following traumatic injury was associated with an average length of stay (LOS) increase of 2 days [15], as poor psychological health in general was associated with an increased LOS in several studies [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…24 Two papers describe case vignettes of patients who had exacerbations of their PTSD while in the Intensive Care Unit (ICU), although neither contain frequency or severity data. 25,26 Approximately 8% of patients in VA ICUs have PTSD, 27 and a published abstract suggests that they appear to require more sedation than do patients without PTSD. 28 Another published case report describes a patient with recurrent PTSD symptoms (nightmares) after moving into a nursing home.…”
Section: The Literature About Ptsd In Hospitalized Patientsmentioning
confidence: 99%